Invasive Fungal Infections in Acute Promyelocytic Leukemia on Dual Differentiating Agents: Real World Data - Yanamandra, Uday (Indian J Hematol Blood Transfus, 2017)
Invasive fungal infection (IFI) in patients with acute promyelocytic leukemia (APL) is a common phenomenon in developing countries. In a systematic study (Dual Inducing Differentiating agents—Indian Trial: DID-IT) using dual differentiating agents (ATO and ATRA) in 98 APL patients at our center we report 18.3% incidence of IFI (n-18). Among all cases of IFI three were definitive, 14 were probable and one was possible IFI. We conclude that incidence of IFI in APL is affected by environmental and therapy related factors and mere usage of dual differentiating agents need not necessarily decrease the incidence of fungal infections.